Implementation of Character Building Training in the Framework of Cultivating a Moderate Attitude of Religion in Students - Makmur, Makmur; Hasis, Pertiwi Kamariah; Rizal, A. (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study examines the implementation of Character Building Training (PPK) and the content delivered. This qualitative study involved 60 students, and eight lecturers selected using purposive sampling and snowball sampling techniques, with data collection considered sufficient if it has reached saturation point. Data was collected through observation and in-depth interviews from June to September 2022. Data analysis was carried out manually using the Discovering Cultural Themes model, including data reduction, data presentation, and drawing conclusions and verification. The study results indicate that PPK is implemented through a PPK campaign cycle, capacity building, and institutionalization with an approach including mentoring, learning, guidance, and support. The content includes attitudes and values, skills, knowledge, and integrative moderate insights, strengthening tolerant, open, critical, caring, and creative behavior, respecting differences, and behaving politely. The CBT program has specifically strengthened the religious character and love of the homeland, with the most significant improvements in this area. The implications and contributions of this study highlight the importance of continuous character education among youth as a tool to strengthen religious moderation.